Development of Learning Cycle 7E-Based Teaching Materials on the Topics of Cartesian Coordinates - Bela, Maria Editha; Wewe, Melkior; Suka, Felista Ripo (FKIP Universitas Lampung, 2023)
Abstract: This research aims to develop and produce teaching materials. The teaching material in question is the Cartesian coordinates module for class VIII junior high school students. This Cartesian coordinate module is based on the 7e learning cycle model which meets valid and practical criteria. This research was carried out at SMP Negeri 5 Bajawa with the test subjects being class VIII students as potential product users. This development research uses the ADDIE development model which consists of five stages, namely Analysis, Design, Development, Implementation and Evaluation. The assessment instrument in this research uses expert test assessment sheets with the aim of measuring the level of validity of teaching materials as well as student and teacher response questionnaires with the aim of measuring the level of practicality of the teaching materials being developed. The research results show that the average validity score for teaching materials is 4.3 with the criteria